Pengaruh Harga dan Fitur Handphone Blackberry Terhadap Tingkat Kepuasan Mahasiswa (Study Kasus Mahasiswa Universitas Esa Unggul Angkatan 2010 Reguler Aktif) - Prasetyoning Tyas, Ari Anggarani Winadi (Lembaga Penerbitan Unversitas Esa Unggul, 2013)
AbstractThis study aims to provide inputs for Blackberry mobile phone manufacturers in the latest innovations in terms of features and applications that support the educational world. This research through the distribution of survey questionnaires to the field with regular students the class of 2010 at the University of Esa Unggul. Variables in this study consists of independent variables (price and feature phone) and the dependent variable (Student Satisfaction). Processing data using multiple regression analysis and partial significant test. The hypothesis of this study consists of the first, Blackberry phones prices affect the level of student satisfaction and second, features of Blackberry mobile phones affect the level of student satisfaction. If the results of the t-test <0.05 then the hypothesis is accepted.Keywords: price, features, level of satisfaction